Assessment of impact of bottlenecks on evacuation in subway stations using network analysis - Jiwon Jeong; Ilwha Lee; Youngseok Oh; Jeryang Park; Seungjun Ahn (Developments in the Built Environment)
In this paper, a novel graph-theory-based analytical framework is introduced, which maps a subway station's spatial configuration into a network model using a space syntax approach. This framework employs Betweenness Centrality (BC) analysis to identify potential bottleneck points in evacuation flows. Various what-if scenarios are tested, including evacuations from the subway station in intact conditions, damaged conditions due to disaster, and improved design for enhanced evacuability. The framework is applied in a case study of Gwanggyo Jungang Station in Korea, which features a typical subway station layout and spatial configuration. Pedestrian simulation models (PSM) are developed and tested for each scenario, allowing for a comparison between the BC analysis results and simulation outcomes. The findings verify the effectiveness of the proposed framework. This integrated approach offers a novel methodical avenue for the quantitative assessment of the evacuability of underground facilities, potentially enhancing subway station designs for better public safety.